2022
DOI: 10.3390/jpm12081305
|View full text |Cite
|
Sign up to set email alerts
|

Depression, Stress, and Suicide in Korean Adults before and during the COVID-19 Pandemic Using Data from the Korea National Health and Nutritional Examination Survey

Abstract: This study investigated changes in the prevalence of depression, stress, and suicidal attempts during the COVID-19 pandemic. The ≥19-year-old population in the Korea National Health and Nutrition Examination Survey in 2019 and 2020 was included. The histories of depression, stress, and suicidal attempts were compared between the 2019 and 2020 cohorts using multiple logistic regression analysis with complex sampling. The prevalence of depression was not significantly different between the 2019 and 2020 groups (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…A total of 8642 studies were screened, with 72 studies (131 samples) meeting the inclusion criteria. Among them, 16 [ 10 , 11 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ], 11 [ 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 ], and 19 [ 8 , 13 , 14 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 ] only addressed changes in suicidal ideation, suicide attempt, and death by suicide, respectively; 25 [ 9 , 12 , 15 , 16 , 92 , 93 , 94 , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 8642 studies were screened, with 72 studies (131 samples) meeting the inclusion criteria. Among them, 16 [ 10 , 11 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ], 11 [ 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 ], and 19 [ 8 , 13 , 14 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 ] only addressed changes in suicidal ideation, suicide attempt, and death by suicide, respectively; 25 [ 9 , 12 , 15 , 16 , 92 , 93 , 94 , …”
Section: Resultsmentioning
confidence: 99%
“… Forest plot for suicide attempt of studies [ 9 , 12 , 15 , 66 , 68 , 72 , 74 , 75 , 93 , 97 , 98 , 99 , 100 , 102 , 108 , 112 , 113 ] conducted in the non-clinical setting (Prismatic colored as red refers to the pooled estimate). …”
Section: Figurementioning
confidence: 99%
“…In the early days of the Covid-19 pandemic, there were studies predicting a negative impact on the mental health of older adults [7,14,15,20]. On the other hand, some studies in the early days of COVID-19 found that depression, stress, and suicide attempts did not change during the COVID-19 pandemic compared to before the pandemic [21,22]. In this study, depression among older adults was 16.3% in 2019, but 23.1% in 2020, 25.7% in 2021, and 21.8% in 2022.…”
Section: Discussionmentioning
confidence: 99%
“…Depression can be a serious health problem that may impair proper functioning at home, school, or work. People with recurrent or severe depression can suffer great distress; in the worst cases, it can lead to suicide attempts [1][2][3]. Due to aging, disease, or job loss, men aged 45 to 54 in particular experience stress and depression.…”
Section: Introduction Backgroundmentioning
confidence: 99%